Decentralized Authorization for Web Services - Stefas, Paraskevas (Trinity College Dublin. Department of Computer Science, 2005)
Web Services is an area that encountered a very sudden and huge explosion on its popularity during the latest years. The advantages Web Services provide compared to traditional distributed computing methods such as Remote Procedure Calls and Distributed Objects were found to be very appealing by researchers and users and this lead to a huge development effort resulting in the creation of many standards and specifications in a rather short period of time. This fact made a lot of security experts to believe that the supporters of Web Services had not given the appropriate consideration on the security aspects of their use. Many analysts showed that the security risks were numerous from such a rapid development without the appropriate attention on security. The response from the Web Services community was the creation of many Workgroups that concentrated their efforts in providing common security mechanisms to Web Services. This dissertation investigates a different approach to Web Services security. We focus on distributed authorization and access control for the development of a security system for Web Services. The result is Web?THER which is a trust management system for Web Services based on the ?THER system that was originally designed for use in a ubiquitous environment. The system is relies on current technologies for the implementation of the Web Service used and is composed by the Web Service and the extra layer that provides the ?THER core functionality. This approach makes the evaluation of this effort easy and comparable to current solutions in the field of Web Services security. The implemented Web Service is a file sharing application. The implementation results are 2014.54 milliseconds average time for the transfer of a 10.4 megabytes file that was used in the Web Service and the average overhead from the inference engine was found to be 6%.
Keywords: Computer Science